Nutritional Status and Anthropometric Indicators as Determinants of Mobility Function among Community-Dwelling Older Adults at Risk of Frailty - Sofia Rhosma Dewi; Dian Ratna Elmaghfuroh (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Frailty is a geriatric condition characterized by a progressive decline in physiological reserves and functional capacity, particularly mobility. Nutritional status and anthropometric indicators play a crucial role in maintaining mobility among older adults; however, integrated evidence focusing on community-dwelling older adults at risk of frailty remains limited. This study aimed to examine the association between nutritional status, mid-upper arm circumference (MUAC), and mobility function among community-dwelling older adults at risk of frailty. Methods: An observational analytic study with a cross-sectional design was conducted among 176 older adults aged ≥60 years who were identified as being at risk of frailty and recruited using consecutive sampling. Nutritional status was assessed using the Mini Nutritional Assessment–Short Form (MNA-SF), MUAC was measured as an anthropometric indicator, and mobility function was evaluated using the Timed Up and Go (TUG) test. Data were analyzed using Chi-square tests and odds ratios (ORs) with 95% confidence intervals. Results: More than half of the participants were classified as at risk of chronic energy deficiency based on MUAC (56.25%), and 52.83% were categorized as malnourished or at risk of malnutrition. Impaired mobility was observed in 69.80% of participants. Significant associations were identified between nutritional status and mobility function (p < 0.001) as well as between MUAC and mobility function (p < 0.001), with very strong associations. Conclusions Early nutritional and anthropometric screening is essential to prevent functional decline and frailty progression among community-dwelling older adults.